2017
DOI: 10.1038/jp.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid procalcitonin as a biomarker of bacterial meningitis in neonates

Abstract: Procalcitonin measurement has diagnostic efficiency similar to the established CSF markers. Routine assessment of procalcitonin in clean non-contaminated CSF may not yield additional information, but it may have clinical utility in situations where diagnosis of meningitis is in dilemma, as in the case of blood contamination of CSF in traumatic lumbar punctures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
0
21
2
Order By: Relevance
“…Reshi et al in their study on neonates observed higher median (interquartile range [IQR]) of CSF PCT in neonates with meningitis in comparison without nonmeningitis. 16 They hypothesized that PCT levels may get raised in blood only when meningitis is accompanied by sepsis. Source of PCT in CSF is likely from the plasma itself as blood-brain barrier gets disrupted due to infectious process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reshi et al in their study on neonates observed higher median (interquartile range [IQR]) of CSF PCT in neonates with meningitis in comparison without nonmeningitis. 16 They hypothesized that PCT levels may get raised in blood only when meningitis is accompanied by sepsis. Source of PCT in CSF is likely from the plasma itself as blood-brain barrier gets disrupted due to infectious process.…”
Section: Discussionmentioning
confidence: 99%
“…Reshi et al reported the median and interquartile of CSF PCT as 0.47 (0.38-0.88) ng/mL in meningitis neonates and 0.26 (0.21-0.28) ng/mL in nonmeningitis neonates. 16 To detect a difference of 0.2 ng/mL between nonmeningitis and confirmed meningitis with 80% power and 5% level of significance using F-test, sample size was calculated to be 17 cases of confirmed meningitis. Considering ratio of sample as 1.5:1.5:1 (non, probable, and confirmed meningitis), we decided to enroll 25 neonates with nonmeningitis, 25 with probable and 17 with confirmed meningitis.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…13 We previously reported that procalcitonin measurement in clean noncontaminated cerebrospinal fluid has diagnostic efficiency similar to the traditional cerebrospinal fluid parameters of total leukocyte count, protein, and sugar. 14 Moreover, routine assessment of procalcitonin in such cases may not yield additional information, but it may have clinical utility in situations where diagnosis of meningitis is in dilemma, as in case of blood contamination of cerebrospinal fluid in traumatic lumbar punctures. However, no comparisons were made with uncorrected and corrected total leukocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…CSF cathelicidin for BM (22)) detected by original mass-spectrometry analysis). Likewise, we did not assess the diagnostic performance of LCN2 against and/or in combination newly proposed biomarkers for CNS infections such as procalcitonin and heparin-binding protein for BM (7, 9, 2325), and CSF lipoarabinomannan for TBM (26). Additionally, we only focused our analysis on adults, leaving the utility potential of LCN2 in pediatric CNS infections unknown.…”
Section: Discussionmentioning
confidence: 99%